Preoperative Statin Use Associated With Lower PSA But Similar Prostate Size and Histopathologic Outcomes: Implications for Active Surveillance? - Stensland, Kristian; McBride, Russell B; Leapman, Michael; Hobbs, Adele; Jazayeri, Seyed Behzad; Samadi, David B (Urology Journal, 2017)
Purpose: The potential effects of statins on clinical and histopathologic variables, prostate size, or PSA density (PSAD) and resulting influences on active surveillance eligibility have not been adequately explored. This study examines the effect of statins on prostate specimens following prostatectomy. Materials and Methods: Patients that received robotic-assisted laparoscopic prostatectomy (RALP) (n = 2,632) were dichotomized according to preoperative statin use. Logistic regression was used to evaluate associations between statin use and patient clinical and pathological characteristics. Results: Men using statins at the time of prostatectomy were older (61.6 ± 6.4 versus 58.8 ± 7.2 years, P < .001), and had poorer health status (P < .001). Biopsy Gleason grade, clinical stage and prostate size were similar among the two groups, although statin users had lower diagnostic PSA levels (5.5 ± 3.6 versus 6.3 ± 4.9 ng/mL, P < .001) and PSAD (.12 versus .13, P = .001). Conclusion: Men taking statins at the time of prostatectomy had similar histopathologic characteristics to non-users, despite having significantly lower serum PSA, being older and having similar sized prostates. This supports prior studies suggesting a PSA reduction effect of statins may warrant consideration of statin usage in decision algorithms for active surveillance.